Factors Associated With Nurses' Performance At The Betungan Care Health Centre In Bengkulu City - Maharani, Nanda; Sari, Fikitri Marva; Darmawansyah, Darmawansyah (Universitas Dehasen Bengkulu, 2024)
Nurse performance is measured by the services provided to patients so that patients feel good or bad about the health services provided by nurses. So nurse performance is the work of nurses in providing nursing care according to their authority and responsibility which can be measured in quality and quantity. Performance can be interpreted through the compliance of professional nurses in carrying out nursing care in accordance with standards. The purpose of this study was to determine the factors associated with the performance of nurses at the Betungan Care Health Centre, Bengkulu City. The method used was a cross sectional design, the data were collected in the form of primary data by distributing questionnaires to 31 nurses at the Betungan Care Health Centre, Bengkulu City using the Total Sampling technique. The results of univariate analysis showed that almost some nurses (45.2%) with vocational education, more than some nurses (58.1%) with good work discipline, almost some nurses (38.7%) with long service period and more than some nurses (61.3%) with good performance. The results of bivariate analysis showed that there was a relationship between education and nurse performance (p=0.029), there was a relationship between work discipline and nurse performance (p=0.001) and there was a relationship between tenure and nurse performance (p=0.014).The researcher suggested that the Puskesmas should be able to motivate its employees at work so that nurse performance becomes good and for the Health Office the results of this study are expected to be used as one of the considerations for making policies or programs in improving the performance of nurses.